2021
DOI: 10.1186/s13104-021-05548-1
|View full text |Cite
|
Sign up to set email alerts
|

Two-stage window screening and development trajectories in early identification of autism spectrum disorder among Han Chinese children

Abstract: Objective An understanding of the trajectory and norm of development in children is needed in order to understand the concept of the spectrum in the diagnosis of autism spectrum disorder (ASD). Children’s developmental growth trajectory was measured from six to 66 months in the Taiwan Birth Cohort Study dataset (N = 11,145). Additionally, over 4 years of follow-up, the negative predictive value of using the Parental Concern Checklist and Taiwan Birth Cohort Study Developmental Instrument was al… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Previous studies of TBCS-DI have shown development at 1.5 years and later to be predictive of children's emotional, cognitive, and social-communicative development at age eight (Lung et al, 2020 ). However, when the diagnosis is put into context, children's developmental trajectories show that language development is unstable before 3 years, and therefore not suitable for ASD diagnosis (Lung and Shu, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of TBCS-DI have shown development at 1.5 years and later to be predictive of children's emotional, cognitive, and social-communicative development at age eight (Lung et al, 2020 ). However, when the diagnosis is put into context, children's developmental trajectories show that language development is unstable before 3 years, and therefore not suitable for ASD diagnosis (Lung and Shu, 2021 ).…”
Section: Discussionmentioning
confidence: 99%